A new species of Myrmedonota Cameron from eastern Kansas (Coleoptera, Staphylinidae, Aleocharinae) - Eldridge, K. Taro (Pensoft Publishers, 2010)

(untitled)
Abstract. Myrmedonota heliantha sp. n. is described from eastern Kansas (USA). All specimens were collected from dung. A modified new key to the species of Myrmedonota of America north of Mexico is provided.